Protecting Cultural Heritage as a Means for International Peace, Security and Stability - Turku, Helga (2016)
Cultural aggression has become a strategy to obtain an advantage during war. In a deliberate and methodical pattern extremists have not only damaged and destroyed historical sites in Iraq and Syria, but they have also looted antiquities to raise money for their terrorist activities. In addition to degrading the victims' identities, such acts decrease the wealth of knowledge of the world as a whole. By examining various treaties and case law on cultural property, this Article highlights the importance of holding these perpetrators accountable. Furthermore, the protection of cultural property in war zones should be an element in the whole strategy for bringing peace, stability, and security to the region. To this end, this Article suggests the creation of a public-private initiative to fight the trafficking of stolen antiquities from conflict zones